Cattle production supplemented on signal grass pastures during the rainy season - Santos, Manoel Eduardo Rozalino; Santos, Anselmo de Deus; Fonseca, Dilermando Miranda da; Sousa, Braulio Maia de Lana; Gomes, Virgilio Mesquita; Sousa, Diogo Olímpio Chaves de (Acta Scientiarum. Animal Sciences, 2016)
The effects of four supplement doses (0, 1, 2 and 3 kg animal-1 day-1) on pasture characteristics and on cattle production on Brachiaria decumbens cv. Basilisk pastures in continuous stocking with variable stocking rate were assessed. Experimental design comprised completely randomized blocks with two replications. Concentrate supplementation did not influence mass (4141 kg ha-1 of DM) and production rate of forage (97.6 kg ha-1 day-1 of DM), morphological components and nutrition value in hand-plucked forage. Similarly, the number of live (1.607 tillers m-²) and dead (636 tillers m-²) tillers was not affected by concentrate supplementation. There were linear increases in animal performance (from 0.70 to 1.13 kg animal-1 day-1), stocking rate (1.9 to 3.8 animal unit ha-1) and animal production per area (1.8 to 6.2 kg ha-1 body weight) with supplementation doses. Concentrate supplementation does not change the structural characteristics of signal grass pastures managed in continuous stocking at 20 cm high, but increases animal production.